TikTok Promotion's Impact on Purchase Decisions with Purchase Interest as Intervening Variable - Rachmad Dwi Afandi Arif; Veni Rafida; Tri Sudarwanto (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the influence of Tiktok promotions on Hanasta Babyshop consumer purchasing decisions, through purchase interest as an intervening variable. Quantitative methods have been used in this research, through distributing questionnaires to the Hanasta Babyshop consumer populations. The number of samples 146 respondents obtained through techniques of simple random sampling. Path analysis has been used and the results of this research show that Tiktok promotions influence purchasing decisions, Tiktok promotions influence purchasing interest, purchasing interest influences purchasing decisions, purchasing interest mediates the influence of Tiktok promotions on purchasing decisions.